2014
DOI: 10.1097/sle.0b013e3182a83493
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and Management of Splenic Injury After Colonoscopy

Abstract: This study reviewed all single experience of splenic injuries after colonoscopy in the last 40 years to define the possible risk factors and the management of this complication. A MEDLINE and a PubMed search was undertaken to identify articles in English, French, Spanish, and Italian from 1974 to 2012 using the key words: "splenic injury," "splenic rupture," and "colonoscopy." Data were analyzed using descriptive statistic. A total of 103 cases have been described in 75 reports. The majority of the patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
103
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(115 citation statements)
references
References 27 publications
2
103
0
7
Order By: Relevance
“…Splenic artery angiography with embolization is a viable alternative to surgical intervention in patients who are hemodynamically capable of tolerating the angiography (22). Although one previous publication found a 93% success rate in patients with traumatic spleen injury with angiography, results of angiography in colonoscopically induced injury has been mixed (9,23). Hemodynamically unstable patient should be taken for operative management.…”
Section: A B Cmentioning
confidence: 99%
“…Splenic artery angiography with embolization is a viable alternative to surgical intervention in patients who are hemodynamically capable of tolerating the angiography (22). Although one previous publication found a 93% success rate in patients with traumatic spleen injury with angiography, results of angiography in colonoscopically induced injury has been mixed (9,23). Hemodynamically unstable patient should be taken for operative management.…”
Section: A B Cmentioning
confidence: 99%
“…Regarding the etiology of surgical spleen injuries (type of procedures and surgeries), it was found evidencesuggesting prevalence of 0.5 % in upper tract urological laparoscopic surgery, recognized intraoperative in 85.7 % (Evidence level type 4) (Chung et al, 2011); left nephrectomy 4.0 to 14.5 % (Evidence level type 4) (Cassar & Munro, 2009;Coon, 1990;Tan et al, 2011); during elective left hemicolectomy in 0.24 % to 8.0 % (Evidence level type 4) (Coon, 1990;Malek et al, 2007;Holubar et al, 2009;Cassar & Munro, 2009;Merchea 2012;Masoomi et al, 2012); during antireflux surgery in 2.0 to 20 %, depending on characteristics of patients (Evidence level type 4) (Coon, 1990;Urschel, 1993;Flum et al, 2001;Cassar & Munro, 2009); during abdominal vascular surgery 21.0 to 60.0 % (Evidence level type 4) (Eaton et al, 2000;Cassar & Munro, 2009;Coon, 1990); in the course of surgery for gastric and duodenal ulcers injuries of the spleen were found in 1.4 % of patients (Evidence level type 4) (Nikolaev et al, 1990); as a complication of upper gastrointestinal endoscopy, ERCP and colonoscopy (Evidence level type 3a and 4) (Piccolo et al, 2014;Ong et al, 1991;Kamath et al, 2009;Ha & Minchin, 2009;Paredes et al, 2013); in the course of laparoscopic cholecystectomy (Evidence level type 4) (Bracale et al, 2013;Geraci et al, 2014); as a complication of bariatric surgery, were found in 0.21 % of patients (Evidence level type 5) (American Society for Metabolic & Bariatric Surgery, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-nine articles in extensive were discarded for failing to meet the eligibility criteria. Finally, the population in study consisted of 35 articles, 3 of evidence level type 3a (Renzulli et al, 2009;He et al, 2014;Piccolo et al, 2014), 32 of evidence level type 4 (Bagrodia et al, 2014;Barmparas et al, 2015;Bracale et al, 2013;Cassar & Munro, 2009;Coon, 1990;Chung et al, 2011;Davies et al, 2014;Eaton et al, 2000;Eber et al, 1999;Edgren et al, 2014;Flum et al, 2001;Geraci et al, 2014;Gómez Alonso et al, 2001;Ha & Minchin, 2009;Harbrecht et al, 2008;Holubar et al, 2009;Kamath et al, 2009;Malek et al, 2007;Masoomi et al, 2012;McIntyre et al, 2005;Merchea et al, 2012;Nikolaev et al, 1990;Ong et al, 1991;Paredes et al, 2013;Rogers et al, 1980;Singla, et al, 2012;Tan et al, 2011;Urschel, 1993;Wang et al, 2011;Yong et al, 2010; and 1 of evidence level type 5 (American Society for Metabolic & Bariatric Surgery, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The most frequent complications are bleeding and perforation, with estimated incidences of 1.8-2.5% and 0.34-2.14%, respectively [1] . Splenic rupture is a rare complication, with 103 cases published until the end of 2012 [1] .…”
Section: Introductionmentioning
confidence: 99%
“…Colonoscopy is a safe, well-tolerated and low-risk diagnostic and therapeutic procedure [1] . The most frequent complications are bleeding and perforation, with estimated incidences of 1.8-2.5% and 0.34-2.14%, respectively [1] .…”
Section: Introductionmentioning
confidence: 99%